Tailored Buckling Constrained by Adjacent Members. (November 2018) - Virgin, Lawrence
Abstract: This paper exploits the accuracy and versatility of additive manufacturing to display interesting buckling behavior in slender elastic columns. A set of parallel columns were printed to relatively high precision, and then subjected to axial loading. The load-deflection behavior is influenced by the post-buckled mutual contact between adjacent columns. Given the capability of incorporating prescribed (but small) initial geometric imperfections using additive manufacturing it is feasible to seed post-bucking behavior, effectively tailoring stiffness.